Antioxidant and cytotoxic properties of protein hydrolysates obtained from enzymatic hydrolysis of Klunzinger's mullet (Liza klunzingeri) muscle - Sana Rabiei; Masoud Rezaei; Samira Asgharzade; Mehdi Nikoo; Mahmoud Rafieia-kopai (Universidade de São Paulo, 2019)
Today, consumers are looking for functional foods that promote health and prevent certain diseases in addition to provide nutritional requirements. This study aimed to evaluate the antioxidant and cytotoxic properties of Liza klunzingeri protein hydrolysates. Fish protein hydrolysates (FPHs) were prepared from L. klunzingeri muscle using enzymatic hydrolysis with papain at enzyme/substrate ratios of 1:25 and 1:50 for 45, 90 and 180 min. The antioxidant activities of the FPHs were investigated through five antioxidant assays. The cytotoxic effects on 4T1 carcinoma cell line were also evaluated. The amino acid composition and molecular weight distribution of the hydrolysate with the highest antioxidant activity were determined by HPLC. All six FPHs exhibited good scavenging activity on ABTS (IC50=0.60-0.12 mg/mL), DPPH (IC50= 3.18-2.08 mg/mL), and hydroxyl (IC50=4.13-2.07 mg/mL) radicals. They also showed moderate Fe+2 chelating capacity (IC50=2.12-12.60 mg/mL) and relatively poor ferric reducing activity (absorbance at 70 nm= 0.01-0.15, 5 mg/mL). In addition, all hydrolysates showed cytotoxic activities against the 4T1 cells (IC50=1.62-2.61 mg/mL). 94.6% of peptide in hydrolysate with the highest antioxidant activity had molecular weight less than 1,000 Da. L. klunzingeri protein hydrolysates show significant antioxidant and anticancer activities in vitro and are suggested to be used in animal studies.